2021
DOI: 10.2147/opth.s285013
|View full text |Cite
|
Sign up to set email alerts
|

Maculopathy Secondary to Pentosan Polysulfate Use: A Single-Center Experience

Abstract: Aim: To investigate the prevalence of retinal pathology in patients with a history of exposure to pentosan polysulfate sodium (PPS). Methods: Patients exposed to PPS and seen in the ophthalmology clinic at Northwestern University during 1/1/2002 to 1/1/2019 were identified from electronic health records (EHR) by an electronic data warehouse (EDW) search. Visual acuity (VA), reasons for clinic visit, ocular conditions, and duration of exposure to PPS were noted. Chart review was performed for fundus exam findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…A similar prevalence of 2.0% (4 out of 216) was reported by Higgins et al, 49 who conducted a chart review of a quaternary academic medical centre electronic medical record database. Kalbag et al 50 described a prevalence of 1.5% (10 out of 131) based on electronic health record data.…”
Section: Data On Prevalence Are Based On Several Prospective Cohort S...mentioning
confidence: 99%
“…A similar prevalence of 2.0% (4 out of 216) was reported by Higgins et al, 49 who conducted a chart review of a quaternary academic medical centre electronic medical record database. Kalbag et al 50 described a prevalence of 1.5% (10 out of 131) based on electronic health record data.…”
Section: Data On Prevalence Are Based On Several Prospective Cohort S...mentioning
confidence: 99%
“…7 Subsequent studies independently conducted at numerous centers have reported a significant dose-response relationship between PPS exposure and presence of maculopathy. [8][9][10][11][12][13] A study from 2020 demonstrated prevalence rates of 13%, 30%, and 42% among patients with 500-999 grams (g), 1000-1499 g, and >1500 g of cumulative PPS exposure, respectively. 8 In another study from earlier this year, researchers found prevalence rates of 46% and 83% among patients with cumulative PPS exposures of 1500-2000 g and ≥2000 g. 11 Studies of large administrative claims databases have yielded mixed findings.…”
Section: Strength Of Associationmentioning
confidence: 99%